Model Pembelajaran Generatif Untuk Meningkatkan Kemampuan Representasi Matematis Peserta Didik - Septi Lestari; A Andinasari; Allen Marga Retta (IndoMath: Indonesia Mathematics Education, 2020)
This study aims to improve the representation ability by using generative learning models in 31 state junior high school in Palembang. The method used in this study is a Quasi experimental design with Randomized pretest-posttest, with a sample consisting of class VII.1 as an experimental class taught with generative learning model adan class VII.2 as a control class taught with a convensional learning model. Data analysis techniques in this study used N-gain and Independent sample t-test analysis. The result of this study indicate that there is an increase in the mathematical representation ability of students who get generative learning models with a N-gain of 0.70 than those who get conventional learning models with a N-gainÂ  of 0,38 in 31 state junior high schools in Palembang.